Smoking-induced change in intrasynaptic dopamine concentration: Effect of treatment for Tobacco Dependence - Brody, Arthur L.; London, Edythe D.; Olmstead, Richard E.; Allen-Martinez, Zoe; Shulenberger, Stephanie; Costello, Matthew R.; Abrams, Anna L.; Scheibal, David; Farahi, Judah; Shoptaw, Steven; Mandelkern, Mark A. (Psychiatry research. Neuroimaging, 2010)
The aim of this study was to determine whether standard treatments for Tobacco Dependence affect smoking-induced changes in intrasynaptic dopamine (DA) concentration. Forty-three otherwise healthy adult cigarette smokers (10 to 40 cigarettes per day) were treated with either practical group counseling (PGC) psychotherapy ( n = 14), bupropion HCl ( n = 14), or matching pill placebo ( n = 15) (random assignment) for 8 weeks. Before and after treatment, each subject underwent a bolus-plus-continuous-infusion 11C-raclopride positron emission tomography (PET) scanning session, during which he or she smoked a regular cigarette. The PET scanning outcome measure of interest was percent change in smoking-induced 11C-raclopride binding potential (BP ND) in the ventral caudate/nucleus accumbens (VCD/NAc), as an indirect measure of DA release. Although the entire study sample had a smaller mean smoking-induced reduction in VCD/NAc BP ND after treatment (compared to before treatment), this change was highly correlated with smaller total cigarette puff volumes (and not other treatment variables). These data indicate that smoking-induced DA release is dose-dependent, and is not significantly affected by reductions in daily smoking levels or treatment type.